Single Exponential Smoothing for Forecasting Medium Rice Retail Prices in Lampung Province - Tuti Maynur Cahya; Bernadhita Herindri Samodera Utami; Felicia Andrade Paskalia Marpaung; Dwi Herinanto (Sciencestatistics: Journal of Statistics, Probability, and Its Application, 2026)
Forecasting the price of medium grade rice is a strategic effort to support decision-making in maintaining food price stability in Lampung Province. This study aims to apply the Single Exponential Smoothing (SES) method in forecasting medium grade rice’s retail price in 2023 by evaluating the performance of the model using Mean Absolute Error (MAE). The data used is monthly retail price data for medium grade rice obtained from Dinas Ketahanan Pangan, Tanaman Pangan, dan Horticultura of Lampung Province. To obtain optimal forecasting results, the forecasting process involves determining the smoothing factor (α) parameters. The results show that the SES method can provide accurate forecasting with low MAE values. These findings suggest that the Single Exponential Smoothing method is feasible to be applied as a tool in food price control and policy planning in Lampung province.